I skuggan av gentrifiering: Offentligt rums tillgänglighet i Vesterbro, Köpenhamn - Bergman,Vendela (2026)
This study aims to understand the impact gentrification might have on the access to public space, and to understand if it differs between socioeconomic groups or stages of gentrification. The study focuses on Vesterbro, Copenhagen, where three public spaces were chosen for the research. Maria Kirkeplads, Halmtorvet and Flæsketorvet, were studied through observations, document analysis and mapping. Theoretically, the study draws on critical theories on public space to analyse the collected data. As a result, it is concluded that access to public space in Vesterbro differs between the analysed areas. While the public space in Vesterbro is somewhat limited for certain socioeconomic groups today, these groups' access to public space was heavily impacted by policies during the 1990s. Furthermore, the analysis shows that marginalised groups today have limited accessibility to certain areas, such as Flæsketorvet, while Halmtorvet and Maria Kirkeplads are more accessible. Even though access to public space has increased to a certain extent, the gentrification through urban renewal still affects the use of land through privatization, commodification and lacking amenities. In the end, this is a question of the right to the city.
Keywords: Offentligt rum; tillgänglighet; gentrifiering; rätten till staden